2014
DOI: 10.47102/annals-acadmedsg.v47n10p420
|View full text |Cite
|
Sign up to set email alerts
|

Periorbital Cellulitis in Paediatric Emergency Medicine Department Patients

Abstract: cellulitis is defined as an infection in front of the orbital septum of the eye and is characterised by development of acute eyelid oedema, tenderness, warmth, chemosis and erythema. [1][2][3] This is a relatively common condition seen in the paediatric population. 4 Periorbital cellulitis has to be promptly distinguished from orbital cellulitis which is an infection occurring posterior to the orbital septum. 5,6,7 Periorbital cellulitis is usually associated with concurrent local pathologies like chalazion, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…Retrospective studies have reported on the use and the safety of oral antibiotics for all grades of severity of POC. James et al reported 46.8% admission rate for 614 patients with POC who represented after being managed with oral antibiotics on an outpatient basis but this study lacked clarity in risk stratification of POC and the definition of mild POC 17 . Compared to this study, the current study had low admission rate (7%).…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Retrospective studies have reported on the use and the safety of oral antibiotics for all grades of severity of POC. James et al reported 46.8% admission rate for 614 patients with POC who represented after being managed with oral antibiotics on an outpatient basis but this study lacked clarity in risk stratification of POC and the definition of mild POC 17 . Compared to this study, the current study had low admission rate (7%).…”
Section: Discussioncontrasting
confidence: 55%
“…Based on the review of 18 out of 24 guidelines (two paediatric guidelines), the authors found that in 51 acute admitting otolaryngology units, that was lack of clarity on the inclusion of ophthalmology review in the guidelines 7 . Some have included daily temperature checks and daily ophthalmology assessment in their protocol 17 . We opted for daily ambulatory team review for the first 2 days after discharge and telephonic ophthalmology consultation (including sending a photograph of the affected eye to the ophthalmologist on call by the ambulatory care team) followed by face‐to‐face ophthalmology review on day 7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that around 80% of orbital cellulitis and abscess cases are caused by bacterial rhinosinusitis. The minority of cases are caused by trauma, infections of the face, middle ear, tonsils, or teeth [ 41 , 42 ]. Odontogenic infections usually gain access to the orbit through the maxillary sinus and associated facial vasculature.…”
Section: Introductionmentioning
confidence: 99%
“…Periorbital cellulitis (also called pre-septal cellulitis) is an acute infection of the periorbital soft tissues, largely the eyelids, skin and soft tissues anterior to the orbital septum [1]. Patients present with unilateral eyelid swelling and oedema [2]. The infection can start from a primary skin, conjunctival or sinus origin, and may in turn progress beyond the orbital septum posteriorly as orbital cellulitis.…”
Section: Introductionmentioning
confidence: 99%